Case Report: A Novel Non-Reciprocal ALK Fusion: ALK-GCA and EML4-ALK Were Identified in Lung Adenocarcinoma, Which May Respond to Alectinib Adjuvant-Targeted Therapy - Zhai, Xiaoqian; Wu, Qiang; Pu, Dan; Yin, Liyuan; Wang, Weiya; Zhu, Daxing; Xu, Feng (Frontiers in Oncology, 2022)
Anaplastic lymphoma kinase (ALK)-positive non-small-cell lung cancers (NSCLCs) have favorable and impressive response to ALK tyrosine kinase inhibitors (TKIs). However, ALK rearrangement had approximately 90 distinct fusion partners. Patients with different ALK fusions might have distinct responses to different-generation ALK-TKIs. In this case report, we identified a novel non-reciprocal ALK fusion: ALK-grancalcin (GCA) (A19: intragenic) and EML4-ALK (E20: A20) by next-generation sequencing (NGS) in a male lung adenocarcinoma patient who was staged as IIIB-N2 after surgery. After a multidisciplinary discussion, the patient received alectinib adjuvant targeted therapy and postoperative radiotherapy (PORT). He is currently in good condition, and disease-free survival (DFS) has been 20 months so far, which has been longer than the median survival time of IIIB NSCLC patients. Our study extended the spectrum of ALK fusion partners in ALK + NSCLC, and we reported a new ALK fusion: ALK-GCA and EML4-ALK and its sensitivity to alectinib firstly in lung cancer. It is vital for clinicians to detect fusion mutations of patients and report timely the newfound fusions and their response to guide treatment.